The Impacts of Health Transformation Program on Healthcare Workers and Health System - Oya Çelebi Çakıroğlu; Arzu Kader Harmancı Seren (Association of Nurse Managers, 2016)
There has been significant political changes in many developing countries including Turkey as result of globalization phenomenon led by international organisations. In this regard, Health Transformation Program has been put into practice as a macro-sized change in the field of healthcare. Health Transformation Program has affected significantly both healthcare workers and health system in Turkey. In this compilation, it has been aimed to evaluate the current situation by examining the areas that healthcare workers and health system have been affected by Health Transformation Program.